Методика формирования сигналов нейростимуляции в общем пространстве средств сочетанного электромагнитного воздействия на биообъекты - Корсунов, А. Р. (НТУ "ХПИ", 2004)
У статті проаналізовані існуючі засоби нейростимуляції, обгрунтовано пріоритетний метод електроакупунктури та розроблено методи формування необхідних при цьому сигналів стимуляції в комплексі електромагнітного впливу на біооб’єкти.

In article is analysised modern equipment of nerv stimulation, is grounded primary method elektroacupuncture According to Voll (EAV) and manufacture of method forming the necessary signals for stimulation, which enter a complex of electromagnetic influence on biostructure.
Keywords: биоструктура; канал связи; электрическая стимуляция; медико-физиологическа практика